Thin film nanocomposite hollow fiber membranes comprising Na+-functionalized carbon quantum dots for brackish water desalination - Gai, Wenxiao; Zhao, Die Ling; Chung, Tai-Shung (Water research (Oxford), 2019)
We have incorporated Na+-functionalized carbon quantum dots (Na-CQDs) into the polyamide layer via interfacial polymerization reaction and developed novel thin film nanocomposite (TFN) hollow fiber membranes for brackish water desalination. Comparing with the conventional thin film composite (TFC) membranes, the TFN membranes comprising Na-CQDs have a larger effective surface area, thinner polyamide layer and more hydrophilic oxygen-containing groups in the polyamide layer. Besides, the interstitial space among the polyamide chains becomes larger due to the presence of Na-CQDs. As a result, the incorporation of 1 wt% Na-CQDs into the polyamide layer could improve the pure water permeability (PWP) of the membranes from 1.74 LMH/bar to 2.56 LMH/bar by 47.1% without compromising their NaCl rejection of 97.7%. Interestingly, stabilization of the TFN hollow fiber membranes containing 1 wt% Na-CQDs at 23 bar could further promote the PWP to 4.27 LMH/bar and the salt rejection to 98.6% under the same testing conditions due to the deformation of the membranes under a high hydraulic pressure. When using a 2000 ppm NaCl aqueous solution as the feed, the optimal water flux and rejection of the newly developed TFN membranes at 15 bar are 57.65 ± 3.26 LMH and 98.6% ± 0.35% respectively. The Na-CQDs incorporated TFN hollow fiber membranes show promising applications in the field of brackish water desalination. [Display omitted] •Pure water permeability (A value) jumps 47.1% after incorporation of 1 wt% Na-CQDs.•Na-CQDs modify both chemical compositions and morphology of polyamide layers.•High-pressure stabilization of hollow fiber membranes effectively promote Jw and R.•Optimal Jw and R of TFN-(Na-CQDs)-1 achieved at 15 bar are 57.65 LMH and 98.6%.